The Occupational Physician and Medical Liability in Moroccan National Law: A Systematic Review - ABOUZAHIR, Hind; TAHRI, Loubna; BELHOUSS, Ahmed; BENYAICH, Hicham (International Journal of Innovative Research in Medical Science, 2023)
This study underscores the pivotal role of occupational physicians in safeguarding workers' health by identifying and evaluating occupational risks to prevent workplace incidents and diseases. The study conducts a comprehensive literature review across databases. Results illuminate the stringent standards governing occupational physicians in Morocco, subjecting them to civil, criminal, and disciplinary responsibilities in cases of medical negligence. Adherence to ethical principles and a profound understanding of relevant laws, particularly those concerning workplace safety, is imperative. Operating within multidisciplinary teams, occupational physicians navigate intricate organizational structures and consider medical-social aspects. In conclusion, the study underscores the necessity for occupational physicians to adapt to legal and medical advancements, addressing medical responsibility holistically. Staying informed, advocating for quality practices, contributing to worker safety, and championing clear regulations are imperative for shaping the trajectory of occupational medicine.